2010
DOI: 10.1179/003962610x12572516251529
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Network RTK GPS Services in Great Britain

Abstract: As of March 2009, network real-time kinematic (RTK) GPS surveying is available in GreatBritain with the aid of two commercial service providers, Leica's "SmartNet" and Trimble's "VRS Now", both

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…Comparisons of the results of each measurement mode to ALS suggest that the overall shift between the data sets was −2.4 cm. The identical mean results were surprising because other researchers have indicated that reproducible 1.5-3.5 cm GPS height accuracies are obtainable (e.g., [19]). In our test case, VRS measurements exhibited more deviation than did RTK-derived measurements and thus also included larger gross errors.…”
Section: Resultsmentioning
confidence: 65%
“…Comparisons of the results of each measurement mode to ALS suggest that the overall shift between the data sets was −2.4 cm. The identical mean results were surprising because other researchers have indicated that reproducible 1.5-3.5 cm GPS height accuracies are obtainable (e.g., [19]). In our test case, VRS measurements exhibited more deviation than did RTK-derived measurements and thus also included larger gross errors.…”
Section: Resultsmentioning
confidence: 65%
“…However, the summed complex amplitudes of the residual semi-diurnal OTL displacements are greater than 1 mm in the horizontal in most of these same areas. These biases, particularly in the vertical, are of only slightly smaller magnitude than the typical errors in baseline and Network RTK GNSS positioning [21,22], and are even more significant in proportion to the positional uncertainty of short-occupation or rapid static relative GNSS. …”
Section: Single-baseline Gnssmentioning
confidence: 84%
“…Such accuracy is acceptable in many types of work, for instance, landscaping, installing of power cables and pipelines. Edwards et al (2010) examined the accuracy of RTK GPS in their work by taking 6 hours data on six stations. They indicated that the accuracy of using this technique is typically 10-20 mm in horizontal control and 15-30 mm in vertical control.…”
Section: -Introductionmentioning
confidence: 99%